Variação sazonal da abundância de Ecballocystis pulvinata Bohlin em um riacho da região centro-sul do estado do Paraná - Krupek, Rogério Antonio; Branco, Ciro César Zanini [UNESP]; Peres, Cleto Kaveski [UNESP] (My University, 2012)
The temporal dynamics of E. pulvinata and its relation to abiotic variables were evaluated monthly during January to December 2007 in a stream located in the central-southern part of Parana State (25°11′16″S - 51°21′25″W). The abundance of the population in terms of percentage cover was obtained by means of the quadrat technique and the following stream water variables were measured: current velocity, irradiance, depth, substrate type, temperature, oxygen saturation, conductivity, pH and turbidity. The abundance of E. pulvinata was considered high (X = 26.7%), with more development (22-46%) during autumn/winter. The low values (0-0.08) of niche width and the few associations with environmental variables shows that the population evaluated is a generalist with regards to the environment in which it occurs. Factors most strictly related were the water flow and the particle size of the substrate, which positively correlated to the seasonal pattern of the population investigated.
Seasonal variation of abundance of Ecballocystis pulvinata Bohlin in a stream of central-southern region of Parana State
Keywords: Environmental distribution; Macroalgae; Microhabitat; Seasonality